INTERRELATION OF DISCOURSE AND GRAMMAR IN EFL CLASSROOM SETTING - Didi Sudrajat (Center of Language and Cultural Studies [CLCS], 2017)
This article describes relation between grammar and discourse in teaching perspectives. The concept basically examines that grammar and discourse are interrelated and coherence. In the interaction practices, the role of grammar is prominent to interpret meaning from which contexts are based. Meaning is contextual and interpretation comes from the surrounding context. Four dimensions proposed in this article appear to relate grammar and discourse: (1) three dimension grammar of language exist in terms of form, meaning, and function, (2) variations of words structure appear in sentences having direct and indirect objects (dative), (3) modality from which certainty is referred, and (4) verbs indicating future actions e.g. be going to and will are present.